2017
DOI: 10.1093/geroni/igx037
|View full text |Cite
|
Sign up to set email alerts
|

Age of Migration and the Incidence of Cognitive Impairment: A Cohort Study of Elder Mexican-Americans

Abstract: Background and ObjectivesTo explore nativity and age of migration differentials in the incidence of cognitive impairment among older Mexican-Americans.Research Design and MethodsWe employ maximum-likelihood discrete time hazard models to estimate risk ratios of cognitive impairment in a sample of 2,708 Mexican-Americans 65 and older who were cognitively healthy at baseline over a follow-up period of up to 20 years.ResultsLate-life immigrant women have a 46% higher risk of cognitive impairment compared to U.S.-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
(78 reference statements)
4
14
0
Order By: Relevance
“…Cognitive complexities of acculturation associated with midlife migration, such as enhancing socioeconomic status through employment and developing new social relationships, may contribute to cognitive advantages of middle-life immigrants. Similar findings were reported by Garcia et al (2017) using the same dataset, but only among male immigrants. Using a nationally representative sample (HRS), Garcia et al (2020) further documented a higher risk of cognitive impairment among Latina immigrants who migrated before age 18, possibly due to greater exposure to social stressors and acculturative stress in formative preadulthood years.…”
Section: Age At Migration and Cognitive Health: Empirical Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Cognitive complexities of acculturation associated with midlife migration, such as enhancing socioeconomic status through employment and developing new social relationships, may contribute to cognitive advantages of middle-life immigrants. Similar findings were reported by Garcia et al (2017) using the same dataset, but only among male immigrants. Using a nationally representative sample (HRS), Garcia et al (2020) further documented a higher risk of cognitive impairment among Latina immigrants who migrated before age 18, possibly due to greater exposure to social stressors and acculturative stress in formative preadulthood years.…”
Section: Age At Migration and Cognitive Health: Empirical Findingssupporting
confidence: 88%
“…Using a nationally representative sample (HRS), Garcia et al (2020) further documented a higher risk of cognitive impairment among Latina immigrants who migrated before age 18, possibly due to greater exposure to social stressors and acculturative stress in formative preadulthood years. Conversely, a number of regional studies reported increased risks for cognitive impairment among later-life immigrants (migrated after age 50), in samples of foreign-born Mexican women (Garcia et al, 2017), and both men and women (Downer et al, 2018;Monserud, 2018). Lower levels of education, disrupted long-established social networks, and decreased social engagement/activities of later-life immigrants are believed to explain their poorer cognitive outcomes (Downer et al, 2018;Garcia et al, 2017;Monserud, 2018).…”
Section: Age At Migration and Cognitive Health: Empirical Findingsmentioning
confidence: 99%
“…Conversely, older immigrants have more difficulties adapting to U.S. society as they are less likely to speak English, have fewer socioeconomic resources, and have a higher likelihood of physical and cognitive decline, which increases social isolation and dependency on family members (Angel et al, 2017;Garcia, Reyes, et al, 2018;Treas & Mazumbdar, 2002). Upon arrival, older immigrants face numerous barriers to health care which are important for obtaining screening and treatment for depression (Burr et al, 2008;Gerst & Burr, 2012).…”
Section: Migration History and Gendermentioning
confidence: 99%
“…Despite considerable research into racial/ethnic disparities in cognitive functioning among older adults and the role of education in explaining these disparities, less scholarship has examined if the likelihood for CIND and dementia among older Hispanics varies by nativity status (i.e., US-born vs. foreign-born) compared to Whites. Prior research documents the risk for cognitive impairment, rates of cognitive decline, and proportion of years after age 65 lived with cognitive impairment vary by nativity status among older Hispanics (Downer et al 2017; Garcia et al 2017b; Garcia et al forthcoming; Hill, Angel, and Balistreri 2012; Hill et al 2012). However, these analyses only included US-born and foreign-born Hispanics of Mexican origin residing in the Southwest United States, which prevented racial/ethnic and nativity comparisons in cognitive status with older White and Black adults.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between nativity, cognitive functioning, cognitive impairment, and cognitive life expectancies among older Hispanics has been shown to differ between men and women (Downer et al 2017; Garcia et al 2017a; Garcia et al 2017b; Garcia et al forthcoming; Hill, Angel, and Balistreri 2012; Hill et al 2012). Differentiating between CIND and dementia is important because CIND is a less severe stage of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%